2000
DOI: 10.1002/(sici)1097-4687(200006)244:3<167::aid-jmor2>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Development of the hypochord and dorsal aorta in the zebrafish embryo Danio rerio

Abstract: The hypochord of the zebrafish embryo (Danio rerio) emerges at the 9-somite stage as a single row of cells in the dorsomedial endoderm immediately ventral to the notochord. It is recognizable from the 2(nd) or 3(rd) somite and extends along the trunk to the same extent as the somites. A basal lamina surrounds the hypochord and its cells are slightly larger than the nearby endoderm cells. TEM studies have shown that the hypochord cells contain, in addition to mitochondria, well-developed rough endoplasmic retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…This suggests that frem3 expression is activated only when cells of the hypochord become significantly differentiated from a midline precursor population; an observation suggesting characteristic changes in ECM complement when cells of the hypochord differentiate. Similar expression of other ECM components at this stage have previously been noted in zebrafish (Yan et al, 1995;Higashijima et al, 1997) and morphological studies of the hypochord have shown that it develops ultrastructural characteristics of an epithelia, including a well-defined basal lamina (Eriksson and Lofberg, 2000). Mammalian studies suggest that many Fras/Frem interactions also take place in the context of a basement membrane (reviewed in Short et al, 2007).…”
Section: Hypochord Expression Of Frem3supporting
confidence: 68%
“…This suggests that frem3 expression is activated only when cells of the hypochord become significantly differentiated from a midline precursor population; an observation suggesting characteristic changes in ECM complement when cells of the hypochord differentiate. Similar expression of other ECM components at this stage have previously been noted in zebrafish (Yan et al, 1995;Higashijima et al, 1997) and morphological studies of the hypochord have shown that it develops ultrastructural characteristics of an epithelia, including a well-defined basal lamina (Eriksson and Lofberg, 2000). Mammalian studies suggest that many Fras/Frem interactions also take place in the context of a basement membrane (reviewed in Short et al, 2007).…”
Section: Hypochord Expression Of Frem3supporting
confidence: 68%
“…The mesodermal or endodermal origin of the hypochord has been a matter of debate, but a consensus view between disparate anamniote species (including Xenopus laevis, axolotl and zebrafish) has emerged ascribing an endodermal character to this tissue (Cleaver et al, 2000;Eriksson and Lofberg, 2000;Lofberg and Collazo, 1997). Amniotes lack a hypochord but its function in patterning blood vessels may have been taken over by dorsal gut endoderm.…”
Section: Introductionmentioning
confidence: 99%
“…The hypochord is a transient structure sitting immediately between the notochord and the developing aorta, and is believed to contribute to aortic development. 31,32 Compared with control morphants, pthr1 morphant embryos ( Figure 4B) frequently demonstrated defects in Notch signaling in the hypochord (thin arrow). When we quantified the percentage of embryos with such a defect in a blinded manner, we found that defective Notch signaling could be identified in 58% of PTHR1 morphants (n=40), whereas only 5% (1 embryo from 20) of control morphants had any interruption in hypochordal Notch signaling ( Figure 4C).…”
Section: Resultsmentioning
confidence: 99%